2007
DOI: 10.1007/s10551-007-9500-7
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and the Social Enterprise

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
168
2
15

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(198 citation statements)
references
References 54 publications
5
168
2
15
Order By: Relevance
“…Di samping itu, perlunya pemanfaatan program yang ditawarkan oleh lembaga, instansi, swasta, perusahaan/ korporasi sebagai perwujudan tanggung jawab sosial kepada masyarakat atau sering disebut Program CSR (corporate social responsibility). Menurut Cornelius et al (2008) kegiatan CSR berbasis masyarakat lebih sering berkembang baik di sektor swasta usaha kecil menengah (UKM). Penetrasi pasar dengan menghasilkan deferensi produk yang lebih banyak memanfaatkan bahan baku sampah dari masyarakat dan perluasan segmentasi pasar yang dapat membantu untuk mendorong penjualan atas produk industri kreatif.…”
Section: Implikasi Manajerialunclassified
“…Di samping itu, perlunya pemanfaatan program yang ditawarkan oleh lembaga, instansi, swasta, perusahaan/ korporasi sebagai perwujudan tanggung jawab sosial kepada masyarakat atau sering disebut Program CSR (corporate social responsibility). Menurut Cornelius et al (2008) kegiatan CSR berbasis masyarakat lebih sering berkembang baik di sektor swasta usaha kecil menengah (UKM). Penetrasi pasar dengan menghasilkan deferensi produk yang lebih banyak memanfaatkan bahan baku sampah dari masyarakat dan perluasan segmentasi pasar yang dapat membantu untuk mendorong penjualan atas produk industri kreatif.…”
Section: Implikasi Manajerialunclassified
“…This is mentioned and proved by review of past literature reviews which revealed that most researches have focused on external CSR aspects (e.g. community involvement and environment protection) resulting in less attention being focused on internal CSR (Cornelius et al, 2008). Therefore, it is not surprising that the concept of internal CSR is rather vague among researchers and in the academic arena.…”
Section: The Evolution Of Internal Csr and Its Practicesmentioning
confidence: 99%
“…Un análisis al concepto del término "formación" nos remite a la adquisición de habilidades y conocimientos, importantes y necesarios para el desarrollo de tareas en la actividad que los trabajadores hacen, como se señala en la tabla siguiente (tabla nº 1): Cada organización adopta una estrategia global teniendo en cuenta un conjunto de factores económicos y financieros, las nuevas tecnologías, su capacidad de innovación, las características de los productos, la legislación vigente, la cultura corporativa y también nuevas preocupaciones que se presenten (Cornelius et al, 2008). En este contexto la formación se integra, por tanto, en la estrategia de recursos humanos de la organización, ajustándose a su vez la misma en la estrategia global de la empresa (Cardon y Stevens, 2004;Lopes, 2005;Cámara y Castilla, 2005;Weber, 2007;Buller y McEvoy, 2012).…”
Section: Concepto De La Formaciónunclassified